2022
DOI: 10.1111/jfbc.14049
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo ameliorative effects of polyphenols from purple potato leaves on renal injury and associated inflammation induced by hyperuricemia

Abstract: In the present study, the ameliorative effects of polyphenols from purple potato leaves (PSPLP) on hyperuricemia were investigated. HPLC-MS analysis showed that PSPLP was mainly composed of caffeoylquinic acid derivatives (84%). PSPLP inhibited the levels of cytokines (IL-1β, IL-6, and TNFα) in monosodium urate-induced RAW264.7 cells. In vivo, PSPLP significantly inhibited the level of uric acid in hyperuricemia mice from 209.6 to 166.6 μM, and significantly interfered with the activities of xanthine oxidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/antiox13050520/s1, Figure S1: The chemical composition of SPL; Table S1: Compounds identification, compound formula, retention times, measured m/z of molecular and mass fragments (MS 2 ) in SPL; Table S2: Content changes in the phenolic profile in SPLs after each digestion stage. References [60][61][62][63] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/antiox13050520/s1, Figure S1: The chemical composition of SPL; Table S1: Compounds identification, compound formula, retention times, measured m/z of molecular and mass fragments (MS 2 ) in SPL; Table S2: Content changes in the phenolic profile in SPLs after each digestion stage. References [60][61][62][63] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Reduced production of other pro-inflammatory mediators, such as COX-2 and IL-8, induced by MSU crystal has been observed in different cell types cultured with pycnogenol and morin by inactivation of NF-kB signaling pathway ( Table 1 ) [ 81 , 82 ]. Decreased levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) have been determined also in MSU crystal-stimulated macrophages after treatment with polyphenols from purple potato leaves [ 83 ].…”
Section: Beneficial Effect Of Bioactive Compounds In Gout and Hyperur...mentioning
confidence: 99%
“…Previous study indicated that some naturally substance can decrease the UA level in vivo and in vitro (Li et al, 2021; Xiang et al, 2021; Xu et al, 2021). Such as, Camellia japonica bee pollen and potato leaves polyphenols markedly reduce serum UA content via inhibiting UA reabsorption and production in hyperuricemia mice (Sun et al, 2022; Xu et al, 2021). Suitable apigenin (API) treatment could markedly decrease the level of serum UA content by inhibiting the reabsorption in hyperuricemia mice (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%